IMPLEMENTASI MEMBRANE HOLLOW FIBER UNTUK MENINGKATKAN KUALITAS VCO PADA PENGERAJIN VCO - I.K.G. SUGITA; K. Astawa; A.A.I.A. Sri Komaladewi; I.G.N. Priambadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Virgin coconut oil (VCO) is one of the processed coconut oil products. The manufacturing process, especially the filtering process, uses a very simple system. The coconut milk filtering process uses by tissue paper that it arranged in layers. Tissue filtering certainly has a weakness because tissue is produced by a chemical process. This is very possible chemical particles will dissolve in the VCO during the filtering process. The tissue that used also does not have standardization on health. The